Tamarillo (Solanum Betaceum) Application In Food Products - Rahmi Holinesti; Yusniwati Yusniwati; Tuty Anggraini; Daimon Syukri (Universitas Negeri Padang, 2025)
Tamarillo (Solanum betaceum), a fruit native to South America, thrives in the highlands of Indonesia and is rich in bioactive compounds with significant potential for functional food development. This study employs a comprehensive literature review of 108 indexed national and international journals to explore the application of tamarillo in food products. Despite its nutritional benefits—such as high vitamin C, antioxidants, and dietary fiber—tamarillo remains underutilized in culinary applications. Current products incorporating tamarillo include syrup, ice cream, jam, soft candy, jelly, steamed bread, cheese, and yogurt. These products leverage tamarillo’s bioactive properties, such as its antioxidant and anti-inflammatory effects, which contribute to health benefits like improved digestion, immune support, and chronic disease prevention. However, further research is needed to expand its applications and optimize its potential in functional foods